A mitochondria-targeted rhodol fluorescent probe for imaging of hydrogen peroxide in living cells. Issue 21 (18th May 2022) - Lv, Linlin; Luo, Weiwei; Diao, Quanping
Abstract : A new type of fluorescent probe Rhodol-OAc for the specific detection of H2 O2 was synthesized. The probe was also successfully applied to indirectly detect xanthine and glucose, and satisfactory results were achieved. Abstract : Hydrogen peroxide (H2 O2 ) is a main member of reactive oxygen species (ROS) in cells that has a significant impact on various physiological and pathological processes of organisms. Here, we designed and synthesized a new type of fluorescent probe Rhodol-OAc for the specific detection of H2 O2 . The probe had good water solubility, high selectivity and sensitivity to H2 O2, low cytotoxicity, excellent mitochondrial targeting ability, etc. It was successfully applied in the imaging of exogenous and endogenous H2 O2 in living cells. In addition, theoretical calculations were carried out to clarify the luminescence mechanism of the probe. More importantly, we successfully applied the probe to indirectly detect xanthine and glucose, the metabolism of which generates H2 O2, and achieved satisfactory results.